African lineage 1a West Nile virus isolated from crocodiles exhibits low neuroinvasiveness in mice - Kobayashi, Hiroko; Chambaro, Herman; Tabata, Koshiro; Ariizumi, Takuma; Phongphaew, Wallaya; Ndashe, Kunda; Ndebe, Joseph; Fandamu, Paul; Kobayashi, Shintaro; Ito, Naoto; Sasaki, Michihito; Hang'ombe, Bernard M; et al. (Journal of general virology, 2024)
West Nile virus (WNV) is a mosquito-borne flavivirus that causes encephalitis in humans and infects crocodiles, resulting in rashes and neurological signs. In Zambia, two distinct lineages of WNV have been detected in neighbouring areas: lineage 2 in mosquitoes and lineage 1a in farmed crocodiles. Considering the risk of direct or vector-mediated WNV transmission from crocodiles to mammals, it is necessary to elucidate the pathogenicity of WNV strains derived from crocodiles. In this study, WNV was successfully isolated from naturally infected farmed crocodiles (Croc110/2019/1/ZM, Croc110). We then investigated its proliferation and pathogenicity in mice in comparison with a WNV isolate from mosquitoes in Zambia (Zmq16) and two reference strains, including one highly pathogenic (NY99) and one low pathogenic (Eg101) strain. Although viral proliferation in Vero and mammalian neuronal cells was comparable among the strains, Croc110 exhibited low cell-to-cell transmission efficiency. , more than 70% of mice (C57BL/6) intracerebrally inoculated with Croc110 displayed neurological signs, and Croc110-infected mice exhibited similarly high mortality rates as NY99- and Zmq16-infected mice. Meanwhile, comparable virus growth was observed among the strains in the brain. However, the virulence of Croc110 was significantly lower than that of Zmq16 and NY99 following intradermal (ID) and intraperitoneal inoculation. Consistently, Croc110 displayed lower growth than Zmq16 and NY99 in the brain and peripheral tissues after ID inoculation. Our study revealed that the crocodile-derived WNV strain is less neuroinvasive in mice, and it exhibits distinct pathogenicity from the highly pathogenic mosquito-derived WNV strain circulating in Zambia.